Self-thickening asphalt emulsifier, preparation method and application thereof
Patent Information
- Application Number
- CN202311597578.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-28
AI Technical Summary
目前国内防水涂料用乳化沥青与沥青乳化剂,为了提高阴离子乳化沥青与重质碳酸钙的混合稳定性,一般使用电荷较弱的木质素磺酸盐与大量的非离子表面活性剂混合配置而成,或者使用常规两性离子表面活性剂,这种两性离子表面活性剂是用长链烷基叔胺与氯乙酸或氯乙酸钠等反应得到,乳化剂中含有5%-9%的氯化钠等无机盐副产物,无机盐的脱除工艺复杂成本高昂,用其制作出的乳化沥青储存稳定性差,需要外加纤维素醚等增稠剂,但制成涂料的增稠效率较低,增稠剂用量大,长期放置容易表层分水,涂料干燥成膜后,非离子表面活性剂和木质素磺酸盐、氯化钠等无机盐残留在干燥后的涂膜中导致涂膜的耐水黄变效果差、吸水率高、粘接强度降低,削弱了沥青基防水涂料的防水效果、减少了沥青基防水涂料的使用寿命
[0041]本发明的沥青乳化剂为改性松香基结构,具有明显的疏水性,每个乳化剂分子含有三组两性离子团簇,可以提高松香基乳化剂自身水溶性,而且3组亲水基团均为两性结构,具有良好的钙皂分散效果,在碱性条件下制得的乳化沥青为阴离子乳液,能够与阴离子的其他乳液和助剂等混合使用,同时能够改善乳化沥青与钙离子、镁离子等2价金属离子混合的稳定性和机械稳定性,乳化生产过程和涂料分散制作过程可以直接用自来水生产,简化生产流程,降低制作成本,制得的涂料分散均匀无颗粒、粘度高、储存稳定。松香基团多元环结构具有良好的疏水效果,可以提高涂料干燥成膜后的耐水性,提高涂料成膜后的耐水黄变效果。
Smart Images

Figure CN117645840B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of asphalt emulsifier technology, and in particular to a self-thickening asphalt emulsifier, its preparation method, and its application. Background Technology
[0002] Asphalt, a byproduct of petroleum refining, is widely used in road construction and building waterproofing due to its low cost and good hydrophobic and waterproof properties. In building waterproofing, it is primarily used by producing modified bitumen waterproof membranes. However, this process requires on-site heating with an open flame, resulting in high energy consumption during production and construction, safety hazards from open flame application, and the inability to completely avoid localized delamination due to variations in worker technique. Once these delaminations occur, widespread water seepage and leakage can lead to waterproofing failure. With the upgrading of industry standards in building waterproofing, water-based bitumen-based liquid membranes that can be applied at room temperature and do not contain harmful solvents are increasingly used in engineering projects. However, the quality of emulsified bitumen specifically designed for liquid membranes on the market varies greatly, and the variety of dedicated asphalt emulsifiers for liquid membranes is even smaller.
[0003] To increase the thickness of asphalt-based waterproof coatings, a certain proportion of fillers and thickeners (such as heavy calcium carbonate powder) need to be added. Heavy calcium carbonate powder will ionize into positively charged calcium or magnesium ions when it comes into contact with water. However, emulsified asphalt used for waterproofing is generally produced using anionic emulsifiers. When anionic emulsifiers come into contact with positively charged calcium ions, they are prone to flocculation particles or even demulsification under high-speed dispersion conditions. Currently, domestic waterproof coatings use emulsified asphalt and asphalt emulsifiers. To improve the mixing stability of anionic emulsified asphalt and heavy calcium carbonate, they are generally formulated by mixing weakly charged lignin sulfonates with a large amount of nonionic surfactants, or by using conventional amphoteric surfactants. These amphoteric surfactants are obtained by reacting long-chain alkyl tertiary amines with chloroacetic acid or sodium chloroacetate. The emulsifier contains 5%-9% inorganic salt byproducts such as sodium chloride. The removal process of inorganic salts is complex and costly. The emulsified asphalt produced by this method has poor storage stability and requires the addition of thickeners such as cellulose ethers. However, the thickening efficiency of the resulting coating is low, and the amount of thickener used is large. Long-term storage easily leads to surface water separation. After the coating dries and forms a film, the nonionic surfactants and inorganic salts such as lignin sulfonates and sodium chloride remain in the dried film, resulting in poor water resistance and yellowing, high water absorption, and reduced adhesion strength. This weakens the waterproof effect of the asphalt-based waterproof coating and reduces its service life.
[0004] Patent CN 113214159 A discloses a method for preparing an imidazoline-type zwitterionic emulsifier. This method involves directly adding a synthesized alkyl imidazoline intermediate to acrylic acid to generate a zwitterionic emulsifier. Sodium hydroxide is then used to adjust the solution to alkalinity. However, since imidazoline and acrylic acid, as organic base and organic acid respectively, directly contact each other, an acid-base neutralization reaction occurs, competing with the addition reaction and resulting in low conversion efficiency. Furthermore, the imidazoline structure undergoes hydrolysis after prolonged storage in alkaline aqueous solutions. Therefore, the emulsifier's emulsifying ability is relatively weak, resulting in low viscosity and unsatisfactory storage stability of the asphalt emulsion. This necessitates the addition of cellulose ether thickeners and stabilizers. Cellulose ethers have water-absorbing and water-retaining properties, which reduces the water resistance of waterproof coatings, and the resulting emulsified asphalt has a short shelf life.
[0005] Patent CN 114539556 A discloses a method for preparing a cold-mix high-viscosity asphalt emulsifier. It involves the addition of rosin acid and acrylic acid, with each mole of intermediate generating two moles of carboxyl groups. These carboxyl groups react with polyamines to form amides or imidazolines. The amides or imidazolines are then neutralized with organic acids to form salts, yielding a cationic asphalt emulsifier. This method falls under the field of road materials. During construction, the emulsified asphalt can be directly mixed with gravel or spread onto the road surface. However, it cannot be stored long-term as a coating. In the field of building waterproofing, emulsified asphalt needs to be mixed and dispersed evenly with modified emulsions and fillers (such as heavy calcium carbonate powder) and stored stably in containers for more than six months. The modified emulsions (such as acrylic emulsions), wetting agents, dispersants, and thickeners (such as alkali-soluble thickeners) used in the production of asphalt-based coatings are all anionic. The combined use of cationic emulsified asphalt with these anionic agents can lead to emulsion demulsification and clumping, rendering the emulsion unusable.
[0006] Patent EP1721938A2 discloses a compound of rosin derivatives and mineral components for use as an emulsifier in the production of emulsified asphalt for waterproofing or road paving. The structural groups of the rosin derivatives are all simple carboxyl groups, which can be used for low-grade road or waterproof spraying construction. However, the asphalt material has poor high and low temperature performance. When it is used in combination with anionic acrylic emulsions that improve high and low temperature performance and large doses of fillers, it is very easy to produce flocculated particles or even demulsification, so the scope of application is limited. Summary of the Invention
[0007] The purpose of this invention is to provide a self-thickening asphalt emulsifier to solve the above problems. It is formed by the condensation of fumaric rosin or maleic rosin with polyamine to generate three amide structures, and the three amide structures are then added with acrylate to generate multiple zwitterionic hydrophilic clusters.
[0008] The objective of this invention is achieved through the following technical solution:
[0009] A self-thickening asphalt emulsifier, comprising the following general structural formula:
[0010]
[0011] In formula I,
[0012] X represents the structure of fumaric acid rosin or maleic acid rosin;
[0013] R1 to R9 are each independently selected from CH2CH2COO - CH2CH2NH2, CH2CH2OH, H, and at least one of R1 to R9 is CH2CH2COO. - .
[0014] As a preferred embodiment of the present invention, R1 to R9 contain 2-7 CH2CH2COO atoms. - .
[0015] As a more preferred technical solution of the present invention, R1 to R9 contain 3-5 CH2CH2COO atoms. - For example, 3, 4, or 5 CH2CH2COO - .
[0016] A method for preparing a self-thickening asphalt emulsifier, comprising: condensing fumaric rosin or maleic rosin with a polyamine to generate an emulsifier containing three amide structures, and then reacting it with an acrylate to generate an emulsifier containing one or more zwitterionic hydrophilic clusters.
[0017] As a preferred technical solution of the present invention, the preparation method specifically includes the following steps:
[0018] (1) Add fumaric acid rosin or maleic acid rosin to the reaction vessel and heat it. Then add polyamine dropwise while stirring. After the addition is complete, heat it to the reaction temperature and keep it at the temperature for the reaction. After the reaction is complete, remove excess polyamine by vacuuming and cool it down to obtain an intermediate containing three amide structures.
[0019] (2) Add the acrylate dropwise to the intermediate in step (1) while stirring. After the addition is complete, heat to the reaction temperature while stirring, keep the temperature for the reaction, and cool to room temperature after the reaction is complete to obtain the product.
[0020] As a preferred embodiment of the present invention, the emulsifier comprises the following raw material components in parts by weight: the emulsifier comprises the following raw material components in a molar ratio of fumarate rosin or maleate rosin: polyamine: acrylate of 1:(3-5):(1-9). Preferably, the emulsifier comprises the following raw material components in a molar ratio of fumarate rosin or maleate rosin: polyamine: acrylate of 1:(4-5):(2-7).
[0021] More preferably, the emulsifier comprises raw material components in the following molar ratio: fumarate rosin or maleate rosin: polyamine: acrylate in a ratio of 1:(4-5):(3-5).
[0022] Preferably, for example in one specific embodiment, the ratio of fumarate rosin or maleate rosin: polyamine: acrylate is 1:4:4.
[0023] As a preferred technical solution of the present invention, the fumaric rosin is selected from M115, M130 and M120 fumaric rosin from Deqing Jiyuan Synthetic Resin Co., Ltd.
[0024] As a preferred technical solution of the present invention, for example, the maleic rosin is selected from 103#, 105#, 107# and 115# maleic rosin from Sanming Senke New Materials Co., Ltd.
[0025] As a preferred embodiment of the present invention, the polyamine is selected from one or more of ethylenediamine, hydroxyethyl ethylenediamine, and diethylenetriamine;
[0026] And / or, in step (1), after adding fumaric acid rosin or maleic acid rosin to the reaction vessel, the temperature is raised to 90-120°C, preferably 100-110°C;
[0027] And / or, the reaction temperature in step (1) is 150-200℃, preferably 175-185℃, and the reaction time is 120-300min, preferably 150-200min;
[0028] And / or, after the reaction in step (1) is completed, the temperature is lowered to 50-100°C, preferably 80-100°C;
[0029] And / or, when adding polyamine in step (1), the addition time is 30-240 min, preferably 150-210 min.
[0030] As a preferred technical solution of the present invention, the acrylate in step (2) is obtained by reacting acrylic acid with neutralizing alkali. The specific method is as follows: the acrylic acid and neutralizing alkali are mixed evenly under temperature control of 30-90℃ for 20-120 min.
[0031] Preferably, acrylic acid and neutralizing alkali are mixed evenly under temperature control at 35-45°C for 50-70 minutes.
[0032] Preferably, the neutralizing base is selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, triethylamine, and triethanolamine. More preferably, the neutralizing base is selected from sodium hydroxide. More preferably, a 30% sodium hydroxide aqueous solution is used.
[0033] Preferably, the molar ratio of acrylic acid to neutralizing alkali is 1:1-1.5, and more preferably, the molar ratio of acrylic acid to neutralizing alkali is 1:1-1.2.
[0034] As a preferred technical solution of the present invention, when adding acrylate in step (2), the stirring speed is controlled at 30-150 rpm; preferably 60-80 rpm.
[0035] And / or, the acrylate is added dropwise over 20-40 minutes;
[0036] And / or, the reaction temperature is 60-100℃, preferably 80-90℃, and the holding time is 60-180min, preferably 100-140min.
[0037] Application of a self-thickening asphalt emulsifier for the production of emulsified asphalt;
[0038] Preferably, the emulsifier is mixed with water and heated to prepare an emulsifier aqueous solution, which is then mixed evenly with the base asphalt to obtain self-thickening emulsified asphalt;
[0039] Preferably, the emulsifier is prepared by the following method: the emulsifier is mixed with water at a mass ratio of 1.5-2:40-50, heated to 50-60°C, and prepared into an emulsifier aqueous solution; the emulsifier aqueous solution is mixed with base asphalt at a mass ratio of 45-50:50-60, the base asphalt is heated to 130-140°C, and the base asphalt is sheared together with the emulsifier aqueous solution through a colloid mill, and cooled to below 50°C to obtain self-thickening emulsified asphalt;
[0040] The self-thickening emulsified asphalt is used to prepare asphalt-based waterproof coatings. Preferably, the self-thickening emulsified asphalt is fully mixed and dispersed evenly with emulsion, dispersant, NXZ defoamer, heavy calcium carbonate powder, AMP-95, thickener, and water to obtain asphalt-based waterproof coatings.
[0041] The asphalt emulsifier of this invention has a modified rosin-based structure, exhibiting significant hydrophobicity. Each emulsifier molecule contains three groups of zwitterionic clusters, which improves the water solubility of the rosin-based emulsifier itself. Furthermore, all three hydrophilic groups are amphoteric, providing excellent calcium soap dispersion. The emulsified asphalt prepared under alkaline conditions is an anionic emulsion, capable of being mixed with other anionic emulsions and additives. It also improves the stability and mechanical stability of the emulsified asphalt mixed with divalent metal ions such as calcium and magnesium ions. The emulsification and coating dispersion processes can be directly produced using tap water, simplifying the production process, reducing costs, and resulting in a uniformly dispersed, particle-free coating with high viscosity and stable storage. The multi-ring structure of the rosin group provides excellent hydrophobicity, improving the water resistance of the coating after drying and film formation, and enhancing its resistance to yellowing after film formation.
[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0043] 1. Emulsified asphalt and asphalt-based coatings made using the emulsifier of this invention have high viscosity and are self-thickening, eliminating the need to add thickeners such as cellulose ethers. This improves the anti-sagging effect of asphalt-based waterproof coatings on vertical surfaces, increases the thickness of a single application, and reduces construction steps.
[0044] 2. The anionic emulsified asphalt made using the emulsifier of the present invention has multiple amphoteric ion clusters, and has good stability and mechanical stability against divalent metal ions such as calcium and magnesium ions. When mixed and dispersed with fillers such as heavy calcium carbonate powder, it is not easy to produce flocculated particles or demulsification. The emulsified asphalt can be produced directly with tap water without the need for deionized water.
[0045] 3. The rosin group introduced in this invention has a large hydrophobic group structure, which can improve the water resistance and yellowing effect of the coating film, and improve the adhesion strength and peel strength of water-based asphalt waterproof coating.
[0046] 4. The zwitterionic surfactant of this invention does not contain halide inorganic salts, which can reduce the water absorption rate of the coating, extend the service life of the waterproof layer, and reduce the corrosion of buildings by halide ion coatings.
[0047] 5. The amide group structure in the structure of this invention has a corrosion inhibition effect and can improve the resistance of asphalt coating to corrosion by low concentration of sulfuric acid. Attached Figure Description
[0048] Figure 1 Comparison photos of the effects of emulsified asphalt prepared with emulsifiers on 7 days of heat storage at 50℃;
[0049] Figure 2 Photos of a waterproof coating for emulsified asphalt stored at 50°C for 7 days.
[0050] Figure 3 Photographs showing the water resistance and yellowing appearance of dry film of asphalt waterproof coating after immersion in water at 23°C for 1 hour.
[0051] Figure 4 Photographs showing the appearance of an asphalt waterproof coating after it has dried and been soaked in a 5% sulfuric acid solution for 7 days, then removed and wiped dry. Detailed Implementation
[0052] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0053] This invention addresses the problems of weak emulsification ability, low viscosity of asphalt emulsions, poor storage stability, and incompatibility with other components in existing asphalt emulsifiers by proposing an improved emulsifier solution.
[0054] Through in-depth research, the inventors discovered that rosin acid can be used as an asphalt emulsifier to produce emulsified asphalt, and the resulting asphalt emulsion has a thickening effect. However, rosin acid has only one carboxyl structure, making it highly sensitive to calcium and magnesium ions in fillers and water. During coating dispersion, it easily produces particles and can even cause emulsion breakdown. Its effectiveness is also poor when used in combination with nonionic surfactants. Amphoteric surfactants, on the other hand, exhibit anionic properties under alkaline conditions and have good calcium soap dispersibility. However, conventional amphoteric surfactants result in low viscosity and poor emulsion stability in emulsified asphalt, and also have other drawbacks. Excessive impurities such as chloride inorganic salts affect the water resistance of the coating. Rosin acid has a relatively large lipophilic group, resulting in a slow dissolution rate in aqueous solution. Therefore, maleic rosin or fumaric acid rosin with more hydrophilic groups is selected to convert it into multiple zwitterionic clusters, which has a better calcium soap dispersion effect. Grafting amine groups with acrylates instead of chloroacetic acid salts can avoid the introduction of by-product chloride inorganic salts. Experiments have shown that the emulsified asphalt made with it has self-thickening and good emulsified asphalt stability, and the coating has better water resistance and a certain degree of resistance to low-concentration sulfuric acid corrosion.
[0055] Based on the above findings, this invention provides a self-thickening and thickening asphalt emulsifier and its preparation method. The preparation method of the self-thickening asphalt emulsifier includes the following steps:
[0056] (1) Add fumaric acid rosin or maleic acid rosin to the reaction vessel, heat to 90-120℃, then add polyamine dropwise under stirring, keep warm for 120-300 min, remove the remaining polyamine by vacuum, cool to 50-100℃, and obtain the first intermediate containing amide structure.
[0057] (2) Acrylic acid and neutralizing alkali (sodium hydroxide, potassium hydroxide, ammonia, triethylamine, triethanolamine, etc.) are slowly mixed evenly under temperature control for 20-120 min and 30-90℃ to obtain the second intermediate, namely acrylate.
[0058] (3) The second intermediate is slowly added dropwise to the first intermediate while stirring. After the addition is complete, the temperature is raised to 60-100℃ while stirring, and kept at that temperature for 60-180 minutes. After the temperature is kept at that temperature, the mixture is cooled to room temperature to obtain the final product.
[0059] The above technical solution will be illustrated by more specific embodiments below.
[0060] Example 1
[0061] A method for preparing a self-thickening asphalt emulsifier specifically includes the following steps:
[0062] S1. Weigh the following raw materials: 0.5 mol of 115# Malaysian rosin (Sanming Senke New Materials Co., Ltd.), 2 mol of ethylenediamine, 2 mol of acrylic acid, and 2.1 mol of sodium hydroxide (prepared as a 30% aqueous solution) for later use.
[0063] S2. Heat the 115# rosin weighed in S1 to 110℃, and then add the ethylenediamine weighed in S1 dropwise while stirring. The dropwise addition time is 180 min. After the dropwise addition is completed, heat the temperature to 180℃ and keep it at that temperature for 180 min. Vacuum the remaining polyamine to remove it, and then cool the temperature to 90℃ to obtain the first intermediate.
[0064] S3. The acrylic acid weighed in S1 and sodium hydroxide are slowly mixed evenly under temperature control for 60 minutes and 40°C to obtain the second intermediate.
[0065] S4. The second intermediate obtained in S3 is slowly added to the first intermediate while stirring. The stirring speed is 70 rpm and the addition time is 30 min. After the addition is completed, the temperature is raised to 85℃ while stirring and kept at that temperature for 120 min. After the addition is completed, the mixture is cooled to room temperature to obtain the asphalt emulsifier.
[0066] Application Example 1
[0067] 1.8g of the emulsifier prepared in Example 1 was added to 45g of tap water and heated to 55°C to prepare an emulsifier aqueous solution. 55g of Donghai-70# asphalt was weighed and heated to 136°C, and then sheared together with the emulsifier aqueous solution through a colloid mill for 45s. The outlet was cooled to below 50°C through a heat exchanger to obtain self-thickening emulsified asphalt, which is the emulsified asphalt sample of Example 1.
[0068] 30g of the emulsified asphalt sample from Application Example 1, cooled to room temperature, was thoroughly mixed and dispersed with 30g of BLJ-6098 emulsion (Shanghai Baolijia New Materials), 0.2g of 5040 dispersant (Nopco), 0.2g of NXZ defoamer (Nopco), 30g of 800-mesh heavy calcium carbonate powder, 0.1g of AMP-95 and 0.1g of TT-935 thickener (Rohm and Haas), and 10g of tap water to form the coating sample for Application Example 1.
[0069] Example 2
[0070] A method for preparing a self-thickening asphalt emulsifier specifically includes the following steps:
[0071] S1. Weigh the following raw materials: M130 fumaric acid rosin (Deqing Jiyuan Synthetic Resin Co., Ltd.) 0.5mol, ethylenediamine 2.5mol, acrylic acid 2.5mol, sodium hydroxide 2.7mol (prepared as a 30% aqueous solution), and set aside.
[0072] S2. The M130 fumaric rosin weighed in S1 is heated to 120°C, and then the ethylenediamine weighed in S1 is added dropwise under stirring for 185 min. After the addition is complete, the temperature is raised to 180°C and held for 180 min. The remaining polyamine is removed by vacuuming and the temperature is lowered to 80°C to obtain the first intermediate.
[0073] S3. The acrylic acid weighed in S1 and sodium hydroxide are slowly mixed evenly under temperature control for 70 min at a temperature of 40°C to obtain the second intermediate.
[0074] S4. The second intermediate obtained in S3 is slowly added to the first intermediate while stirring. The stirring speed is 70 rpm and the addition time is 30 min. After the addition is completed, the temperature is raised to 85℃ while stirring and kept at that temperature for 120 min. After the addition is completed, the mixture is cooled to room temperature to obtain the asphalt emulsifier.
[0075] Application Example 2
[0076] Replace the emulsified asphalt sample in Application Example 1 with the emulsifier sample prepared in Example 2, while keeping all other raw materials and conditions unchanged, and prepare the emulsified asphalt sample and coating sample of Application Example 2 accordingly.
[0077] Example 3
[0078] A method for preparing a self-thickening asphalt emulsifier specifically includes the following steps:
[0079] S1. Weigh the following raw materials: 0.5 mol of 115# Malaysian rosin (Sanming Senke New Materials Co., Ltd.), 2 mol of hydroxyethyl ethylenediamine, 2 mol of acrylic acid, and 2.1 mol of sodium hydroxide (prepared as a 30% aqueous solution) for later use.
[0080] S2. Heat the 115# rosin weighed in S1 to 110℃, and then add the hydroxyethyl ethylenediamine weighed in S1 dropwise while stirring. The dropwise addition time is 180 min. After the dropwise addition is completed, heat the temperature to 180℃ and keep it at that temperature for 180 min. Vacuum the remaining polyamine to remove it, and then cool the temperature to 90℃ to obtain the first intermediate.
[0081] S3. The acrylic acid weighed in S1 and sodium hydroxide are slowly mixed evenly under temperature control for 60 minutes and 40°C to obtain the second intermediate.
[0082] S4. The second intermediate obtained in S3 is slowly added to the first intermediate while stirring. The stirring speed is 70 rpm and the addition time is 30 min. After the addition is completed, the temperature is raised to 85℃ while stirring and kept at that temperature for 120 min. After the addition is completed, the mixture is cooled to room temperature to obtain the asphalt emulsifier.
[0083] Application Example 3
[0084] Replace the emulsifier sample in Application Example 1 with the emulsifier sample prepared in Example 3, while keeping all other raw materials and conditions unchanged, and prepare the emulsified asphalt sample and coating sample of Application Example 3 accordingly.
[0085] Example 4
[0086] A method for preparing a self-thickening asphalt emulsifier specifically includes the following steps:
[0087] S1. Weigh the following raw materials: M130 fumaric acid rosin (Deqing Jiyuan Synthetic Resin Co., Ltd.) 0.5mol, diethylenetriamine 2.5mol, acrylic acid 2.5mol, sodium hydroxide 2.7mol (prepared as a 30% aqueous solution), and set aside.
[0088] S2. The M130 fumaric rosin weighed in S1 is heated to 120°C, and then diethylenetriamine weighed in S1 is added dropwise under stirring for 185 min. After the addition is complete, the temperature is raised to 180°C and held for 180 min. The remaining polyamine is removed by vacuuming and the temperature is lowered to 80°C to obtain the first intermediate.
[0089] S3. The acrylic acid weighed in S1 and sodium hydroxide are slowly mixed evenly under temperature control for 70 min at a temperature of 40°C to obtain the second intermediate.
[0090] S4. The second intermediate obtained in S3 is slowly added to the first intermediate while stirring. The stirring speed is 70 rpm and the addition time is 30 min. After the addition is completed, the temperature is raised to 85℃ while stirring and kept at that temperature for 120 min. After the addition is completed, the mixture is cooled to room temperature to obtain the asphalt emulsifier.
[0091] Application Example 4
[0092] Replace the emulsifier sample in Application Example 1 with the emulsifier sample prepared in Example 4, while keeping all other raw materials and conditions unchanged, and prepare the emulsified asphalt sample and coating sample of Application Example 4 accordingly.
[0093] Comparative Example 1
[0094] Commercially available anionic waterproof asphalt emulsifier (a compound of lignin and nonionic surfactants).
[0095] Application Comparative Example 1
[0096] Replace the emulsifier sample in Application Example 1 with the commercially available anionic waterproof asphalt emulsifier of Comparative Example 1, and prepare emulsified asphalt and coating samples according to the same raw material dosage and process as the sample in Application Example 1. These are the samples of Comparative Example 1.
[0097] Comparative Example 2
[0098] Commercially available anionic waterproof asphalt emulsifiers (betaine-based amphoteric surfactants).
[0099] Application Comparative Example 2
[0100] Replace the emulsifier sample in Application Example 1 with the commercially available anionic waterproof asphalt emulsifier of Comparative Example 2, and prepare emulsified asphalt and coating samples according to the same raw material dosage and process as the sample in Application Example 1. These are the samples of Comparative Example 2.
[0101] Comparative Example 3
[0102] Commercially available sodium rosinate (CAS No. 14351-66-7).
[0103] Application Comparative Example 3
[0104] Replace the emulsifier sample in Application Example 1 with commercially available rosin acid emulsifier from Comparative Example 3, and prepare emulsified asphalt and coating samples using the same raw material dosage and process as the sample in Application Example 1. These are the samples of Comparative Example 3.
[0105] Comparative Example 4
[0106] Commercially available cationic rosin amide asphalt emulsifier.
[0107] Application Comparative Example 4
[0108] Replace the emulsifier sample in Application Example 1 with the commercially available cationic rosin amide asphalt emulsifier of Comparative Example 4, and prepare emulsified asphalt and coating samples according to the same raw material dosage and process as the sample in Application Example 1. These are the samples of Comparative Example 4.
[0109] [Performance Testing]
[0110] The performance of the emulsified asphalt samples obtained in the above examples / comparative examples was tested, specifically including:
[0111] Solid content: 5.5% as per JC / T 408-2005;
[0112] Brockfield viscosity of emulsified asphalt: BROOKFIELD viscometer, #2, 60 rpm;
[0113] 50℃, 7-day thermal storage stability: 200ml of emulsion is placed in a transparent container and sealed. It is placed in a 50℃ constant temperature box for 7 days. The state of the emulsified asphalt is observed. No stratification or demulsification is acceptable.
[0114] Pulping stability: The emulsified asphalt and other raw materials in the waterproof coating are mixed and dispersed evenly, with no demulsification and no obvious particulate matter.
[0115] Performance tests were conducted on the coating samples from the above application examples and comparative examples, referring to the group standard T / SZWA006—2021 "Technical Specification for Application of High-Viscosity Anti-skid Waterborne Rubber Asphalt Waterproof Coatings", specifically including:
[0116] Water absorption rate: Refer to 7.12 in JC / T 1017-2020;
[0117] Coating KU viscosity: GB / T 9269;
[0118] Bond strength of concrete blocks: Method 7.1B in GB / T 16777;
[0119] Peel strength: 5.8 according to JC / T 1069-2008;
[0120] Peel strength retention rate after 7 days of immersion in water: After immersion in water for 7 days, the specimen shall meet the requirements of 5.8 in JC / T1069-2008;
[0121] For detailed test results, please refer to Tables 1 and 2.
[0122] Table 1. Performance test results of asphalt emulsifiers
[0123] Technical Requirements ≥50 none Unlayered demulsification pass Example 1 56.7 258.2 Unlayered demulsification pass Example 2 57.8 263 Unlayered demulsification pass Example 3 58.9 273.5 Unlayered demulsification pass Example 4 57.3 269.3 Unlayered demulsification pass Comparative Example 1 54.8 28.9 Top 2 / 5 clear water pass Comparative Example 2 55.3 35.2 The top 1 / 3 is clear water. pass Comparative Example 3 55.6 178.8 Unlayered demulsification Particulate matter Comparative Example 4 55.7 183.2 Unlayered demulsification Breast breaking
[0124] Table 2 Performance test results of coating samples
[0125]
[0126] As shown in Tables 1 and 2, the test results of the embodiments of the present invention are significantly better than those of the comparative examples, especially in terms of the viscosity of emulsified asphalt and the bonding strength of the coating, with significant improvements in various performance indicators.
[0127] Figure 1 Comparative photos of the effects of emulsified asphalt prepared with emulsifiers after 7 days of heat storage at 50°C show that after 7 days of heat storage in a constant temperature chamber at 50°C in Examples 1-4, there was no obvious stratification on the surface, while there was a clear water layer on the upper part of Comparative Examples 1 and 2, and a small amount of slight water layer in Comparative Examples 3 and 4.
[0128] Figure 2 The photos show that the asphalt-based coating made from emulsified asphalt was heated at 50°C for 7 days. It can be seen that the asphalt-based coating made from emulsified asphalt was taken out after being heated in a constant temperature chamber at 50°C for 7 days. Examples 1-4 showed no obvious stratification. Comparative Example 1 had a water layer on the top and the coating separated. Comparative Example 2 also had a water layer on the top. Comparative Examples 3 and 4 showed demulsification.
[0129] Figure 3The images show the appearance of the asphalt waterproof coating dry film after immersion in water at 23°C for 1 hour to prevent yellowing. It can be seen that after immersion in water at room temperature for 1 hour, the coating dry film in Examples 1-4 still remained black, with the color slightly lighter, while the comparative examples 1-2 showed obvious yellowing.
[0130] Figure 4 The photographs show the appearance of the asphalt waterproof coating after it has dried and been soaked in a 5% sulfuric acid solution for 7 days. It can be seen that after soaking the dry coating film in a 5% sulfuric acid solution for 7 days and then wiping it dry, the surface of the example has a small amount of corrosion marks but no bubbles. The surfaces of Comparative Examples 1 and 2 have dense bubbles.
[0131] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A self-thickening asphalt emulsifier, characterized in that, The emulsifier includes the following general structural formula: In Formula I, X represents the structure of fumaric acid rosin or maleic acid rosin; R1 to R9 are each independently selected from CH2CH2COO-, CH2CH2NH2, CH2CH2OH, and H, and at least one of R1 to R9 is CH2CH2COO-.
2. The self-thickening asphalt emulsifier according to claim 1, characterized in that, R1 to R9 contain 2-7 CH2CH2COO-.
3. The self-thickening asphalt emulsifier according to claim 1, characterized in that, R1 to R9 contain 3-5 CH2CH2COO- ions.
4. The preparation method of a self-thickening asphalt emulsifier as described in claim 1, characterized in that, Fumaric acid rosin or maleic acid rosin condenses with polyamines to form a compound containing three amide structures, which then undergoes an addition reaction with acrylates to form an emulsifier containing one or more zwitterionic hydrophilic clusters.
5. The method for preparing a self-thickening asphalt emulsifier according to claim 4, characterized in that, Includes the following steps: (1) Add fumaric acid rosin or maleic acid rosin to the reaction vessel and heat it. Then add polyamine dropwise while stirring. After the addition is complete, heat it to the reaction temperature and keep it at the temperature for the reaction. After the reaction is complete, remove excess polyamine by vacuuming and cool it down to obtain an intermediate containing three amide structures. (2) Add the acrylate dropwise to the intermediate in step (1) while stirring. After the addition is complete, heat to the reaction temperature while stirring, keep the temperature for the reaction, and cool to room temperature after the reaction is complete to obtain the product.
6. The method for preparing a self-thickening asphalt emulsifier according to claim 5, characterized in that, The emulsifier comprises raw material components in the following molar ratio: fumarate rosin or maleate rosin: polyamine: acrylate in a ratio of 1:(3-5):(1-9).
7. The method for preparing a self-thickening asphalt emulsifier according to claim 5, characterized in that, The polyamine is selected from one or more of ethylenediamine, hydroxyethyl ethylenediamine, and diethylenetriamine; And / or, in step (1), after adding fumaric acid rosin or maleic acid rosin to the reaction vessel, the temperature is raised to 90-120℃, and / or, in step (1), the reaction temperature is 150-200℃ and the reaction time is 120-300min. And / or, after the reaction in step (1) is completed, cool down to 50-100℃; And / or, when adding polyamine in step (1), the addition time is 30-240 min.
8. The method for preparing a self-thickening asphalt emulsifier according to claim 5, characterized in that, The acrylate in step (2) is obtained by reacting acrylic acid with a neutralizing alkali. The specific method is as follows: the acrylic acid and the neutralizing alkali are mixed evenly under temperature control at 30-90℃ for 20-120 min. The neutralizing base is selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, triethylamine, and triethanolamine.
9. The method for preparing a self-thickening asphalt emulsifier according to claim 5, characterized in that, When adding acrylate in step (2), the stirring speed should be controlled at 30-150 rpm; And / or, the acrylate is added dropwise over 20-40 minutes; And / or, the reaction temperature is 60-100℃, and the reaction time is 60-180min.
10. The application of the self-thickening asphalt emulsifier as described in claim 1, characterized in that, This emulsifier is used to make emulsified asphalt; The emulsifier is mixed with water and heated to prepare an emulsifier aqueous solution, which is then mixed evenly with the base asphalt to obtain a self-thickening emulsified asphalt. And / or, the self-thickening emulsified asphalt is used to prepare asphalt-based waterproof coatings: the self-thickening emulsified asphalt is fully mixed and dispersed with emulsion, dispersant, NXZ defoamer, heavy calcium carbonate powder, AMP-95, thickener, and water to obtain asphalt-based waterproof coatings.
Citation Information
Patent Citations
Preparation method of asphalt emulsifier
CN113214159A
Emulsifier for bituminous binders
EP1721938A2
Emulsifier for cold-mixed high-viscosity emulsified asphalt and preparation method thereof
CN114539556A
Rosin cation asphalt emulgent
CN1861721A